The Phytosociology of Tree Communities on Two Mounts in Bedugul Highland Tropical Forest, Bali, Indonesia - Atmaja, Muhammad Bima; Sutomo; Humaida, Nida; Pujiono, Eko; Saputra, M. Hadi; Sukmawati, Jalma Giring; Hani, Aditya; Iryadi, Rajif; Herningtyas, Wieke; Hadiyan, Yayan; Januar, Hedi Indra; Hidayah, Izhamil (Media Konservasi, 2025)
The forested regions within the Bedugul highland stand as some of the last remaining tropical mountain rainforests in Bali. However, recent development in Bedugul indicates a surge in mass tourism, posing a threat to its diverse plant life due to increased land-use changes and overpopulation. Hence, this research aimed to ascertain the composition and diversity of tree communities within the Bedugul highland forest, focusing on Mt. Pohen and Mt. Tapak. While Mt. Pohen has a history of disturbances like the establishment of a geothermal power plant and forest fires, Mt. Tapak experiences comparatively less disruption. The methods include species identification, the diversity index calculation, the species composition and abundance, and the similarity analysis between permanent sample plot (PSP) from Mt. Pohen and PSP from Mt. Tapak. The result shows a clear separation in tree species composition and abundance between both PSPs. Some species are only detected at Tapak but absent at Pohen or vice versa. However, Euphorbiaceae is the dominating family in both mounts, as the species are known as pioneer plants that benefit in growth and adaptation to the highland habitat after disturbance. The most abundant species in a one-hectare plot on Mt. Pohen are Crypteronia paniculata and Acronychia trifoliata. While on Mt. Tapak, it appears to be Dendrochnide stimulans. Both mounts are occupied mainly by tree groups with diameters ranging from 10 to 20 cm.